Nucleus Pulposus Cells Induce M2 Polarization of RAW264.7 via CX3CL1/CX3CR1 Pathway and M2 Macrophages Promote Proliferation and Anabolism of Nucleus Pulposus Cells - Xiao-Tao Wu; Bo-Wen Wan; Xin-Min Feng; Yu-Ping Tao; Yong-Xiang Wang; Hui-Hui Sun (Hindawi Limited, 2023)
Background. The mechanisms underlying M2 macrophage polarization induced by nucleus pulposus (NP) cells are unclear. The effects that M2-polarized macrophages have on NP cells are also controversial. Methods. Transcriptome sequencing was performed to detect the gene change profiles between NP cells from ruptured intervertebral disc (IVD) and normal IVD. The main difference on biological activities between the two cell groups were analyzed by GO analysis and KEGG analysis. Virus transduction, flow cytometry, immunofluorescence, RT-PCR, western blot, CCK-8, TUNEL staining, and AO/EB staining were performed to explore the interactions between NP cells and RAW264.7 macrophages. Statistics were performed using SPSS26. Results. 801 upregulated and 276 downregulated genes were identified in NP cells from ruptured IVD in mouse models. According to GO and KEGG analysis, we found that the differentially expressed genes (DEG) were dominantly enriched in inflammatory response, extracellular matrix degradation, blood vessel morphogenesis, immune effector process, ossification, chemokine signaling pathway, macrophage activation, etc. CX3CL1 was one of the top 20% DEG, and we confirmed that both NP tissue and cells expressed remarkably higher level of CX3CL1 in mouse models (p<0.001∗). Besides, we further revealed that both the recombinant CX3CL1 and NP cells remarkably induced M2 polarization of RAW264.7 (p<0.001∗), respectively, while this effect was significantly reversed by si-CX3CL1 or JMS-17-2 (p<0.001∗). Furthermore, we found that M2 macrophages significantly decreased the apoptosis rate (p<0.001∗) and the catabolic gene levels (p<0.001∗) of NP cells, while increased the viability, proliferation as well as the anabolic gene levels of NP cells (p<0.01∗). Conclusions. Via regulating CX3CL1/CX3CR1 pathway, NP cells can induce the M2 macrophage polarization. M2 polarized macrophages can further promote NP cell viability, proliferation, and anabolism, while inhibit NP cell apoptosis and catabolism.